2015
DOI: 10.1016/j.bjorl.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

High frequency hearing thresholds and product distortion otoacoustic emissions in cystic fibrosis patients

Abstract: A significant number of patients with cystic fibrosis who received repeated courses of aminoglycosides showed alterations in High Frequency Audiometry and Distortion Product Otoacoustic Emissions. The implementation of ten or more aminoglycoside cycles was associated with alterations in High Frequency Audiometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
0
17
0
2
Order By: Relevance
“…A prospective study in adults investigated the ototoxic detection rate of DPOAEs and behavioural measures (HFA) and reported DPOAEs specificity rate was 78% in ears with confirmed behavioural changes and measurable DPOAEs [ 30 ]. A similar study in children with CF who received aminoglycosides showed higher alterations in HFA compared to DPOAEs [ 33 ]. In contrast, another study concluded that both HFA and DPOAEs showed the same sensitivity in detecting ototoxicity, but did not produce the same results in all patients [ 42 ].…”
Section: Diagnosismentioning
confidence: 94%
See 2 more Smart Citations
“…A prospective study in adults investigated the ototoxic detection rate of DPOAEs and behavioural measures (HFA) and reported DPOAEs specificity rate was 78% in ears with confirmed behavioural changes and measurable DPOAEs [ 30 ]. A similar study in children with CF who received aminoglycosides showed higher alterations in HFA compared to DPOAEs [ 33 ]. In contrast, another study concluded that both HFA and DPOAEs showed the same sensitivity in detecting ototoxicity, but did not produce the same results in all patients [ 42 ].…”
Section: Diagnosismentioning
confidence: 94%
“…1 shows the proposed ototoxicity monitoring protocol. Most studies have found HFA is a more sensitive tool in the early identification of ototoxic changes than PTA [ 24 , 31 - 33 ]. Length of testing is the major limitation of behavioural threshold monitoring.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…This drug is known to be cochleotoxic. 8 , 21 The incidence of hearing loss varies greatly and may depend on genetic factors, individual susceptibility, the type of assessment used, and the criteria established to define hearing loss. 10 Early detection of ototoxicity enables changes to be made to the drug regimen in order to stabilize damage to the structures of the ear and prevent further damage to them, thus reducing the chance of impaired psychosocial relationships due to impaired communication.…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, extended high-frequency audiometry, which is more sensitive in detecting early ototoxic effects, is often not routinely performed. 16 There has hence been a technology drive to enable tablet, smartphone or web-based OMPs integrated within the clinical service to streamline care. Recent studies have validated this technology in healthy children and adults, but to date, there are no studies validating their use to detect hearing loss in adults with chronic lung disease.…”
Section: Why Read On?mentioning
confidence: 99%